Seeing through cells: Rapid measurement of intracellular target proteins - Larsson, Per-Olof; Leiva Eriksson, Nelida (Frontiers in Bioengineering and Biotechnology, 2022)
We have studied a method for making microbial cells transparent by immersing them in a solution with a high refractive index (RI). When the RI of the solution was matching that of the cells, light scattering was greatly diminished (by a factor of up to about 100) and the cell suspension became transparent, facilitating the spectrophotometric determination of intracellular compounds such as hemoglobin. We investigated the properties of several compounds such as sucrose, glycerol, bovine serum albumin, FicollTM, and iodixanol (OptiprepTM), each with advantages and disadvantages. Particularly good overall properties were found for iodixanol at a concentration of around 36% (w/v) and bovine serum albumin at a concentration of about 30% (w/v). By using this RI-matching principle the production of intracellular compounds can easily be followed in near real-time during fermentation processes. For example, some conditions for producing plant hemoglobin in Escherichia coli were conveniently determined without the need of any cell disintegration or product purification.